(untitled) (Research, Society and Development, 2020)
The effects of smoking processes on the sensory and proximate components of two species of shrimp were evaluated. Sixty specimens of each species were distributed in a completely randomized design, with two treatments (T1 = hot smoking and T2 = liquid smoking), and fresh shrimps samples were used as control (T3). The sensory characteristics were evaluated using the 9 point hedonic scale and the acceptance index. The centesimal composition was evaluated based on 100 g from each treatment and the fresh samples. The data were submitted to one-way ANOVA and Tukey’s test. The results of sensory analysis showed significant variations (p <0.05) for the attributes analyzed among the species, whereas among the smoking processes there was no significance (p >0,05). The acceptance rate was above 70% for amazonian prawn and 80% for white shrimp, regardless of the smoking method. The proximate analysis showed significant differences between the two smoking processes, hot and liquid, with moderet values of lipids, between 0.27% and 1.51%, and high protein values, of 24.61% 24.13%, for white shrimp and amazonian prawn, respectively. The smoking processes altered the sensory and chemical profile of the prawns, causing good acceptance and adequate nutritional constitution for smoked fish.